Worth keeping global perspectives on best practice in missionary retention - Hay, Rob; Lim, Valerie; World Evangelistic Alliance Mission Commission (Pasadena, CA William Carey, 2007)
Includes bibliographical references and index.
Keywords: Missions; Missionaries